Indirect Determination of Thiocyanate Ions in Seawater by Methyl Isobutyl Ketone Extraction-Atomic Fluorescence Spectrometry - Lu, Jianping; Bu, Jinglong; Ni, Huquan; Huang, Yangjie (Asian Journal of Chemistry, 2014)
The complex of thiocyanate ions and Hg2+ in aqueous phase was extracted into methyl isobutyl ketone, then the organic phase combined with reductant was introduced simultaneously into atomic fluorescence spectrometer, where Hg was determined in terms of thiocyanate ions. The vatiations of extractants, aqueous acidity, volume of extractnt, shaking and rest times were investigated. The experimental results indicated that the extraction efficiency of the complex decremented as the acidity of aqueous phase incremented. On the other hand, it increased as volume of methyl isobutyl ketone increased, then approached to be constant. In optimum condition, the extraction efficiency could reach more than 95 %. The method was linear in the range of 0.2-150 ng/mL, and the minimum detectable limit of 1.33 ng/mL was obtained. This method of high sensitivity and good accuracy was applied to determine thiocyanate ions in seawater.